The Role of Work Engagement and Leader Distance in Transformational Leadership on Student Performance (Jurnal Manajemen Bisnis, 2026)
This study examines the influence of transformational leadership on student performance, with work engagement as a mediating variable and leader distance as a moderating variable. Using a quantitative approach, data were collected from 101 accounting students actively involved in student organizations at Swadaya Gunung Jati University and analyzed using SEM-PLS with SmartPLS 4. The result indicate that transformational leadership positively influences work engagement and student performance. Work engagement partially mediates this relationship, while leader distance moderates the indirect effect. These findings highlight the importance of leadership stle, engagement, and relational proximity in enhancing student performance in higher education.